Vom Slowenischen als Erst- zum Deutschen als Fremdsprache - Leskovec, Mojca (Vestnik za tuje jezike, 2018)
In the history of foreign language didactics, the teaching of grammar and the integration of the mother tongue into foreign language classrooms were treated very differently; in modern foreign language classrooms, however, they have both found their place again. The main goal of foreign language teaching is the development of communicative competence, which according to the Common European Framework of Reference for Languages is formed through interrelation and interaction of all the languages one has learned and for which the grammatical competence is of the utmost importance. This article therefore emphasises two of the many didactic-methodological principles that a foreign language classroom in the post-method era should be based on: action and plurilingual orientation. In a modern foreign language classroom, cognitive learning processes and automatisation, as well as intra- and interlanguage teaching strategies, should complement each another. This article summarises different reasons for inclusion of the latter and shows, based on the example of Slovene as a first and German as a foreign language, how inclusion of the first language can positively influence the understanding of the use of articles in the second or third language.
Keywords: akcijsko usmerjeni pristop; didaktika jezika; materinščina; nemščina; slovenščine; slovnična zmožnost; sporazumevalna zmožnost; tuji jeziki; večjezičnost